4-PBA Treatment Improves Bone Phenotypes in the Aga2 Mouse Model of Osteogenesis Imperfecta - Duran, Ivan; Zieba, Jennifer; Csukasi, Fabiana; Martin, Jorge H; Wachtell, Davis; Barad, Maya; Dawson, Brian; Fafilek, Bohumil; Jacobsen, Christina M; Ambrose, Catherine G; Cohn, Daniel H; Krejci, Pavel; et al. (Journal of bone and mineral research, 2022)
Osteogenesis imperfecta (OI) is a genetically heterogenous disorder most often due to heterozygosity for mutations in the type I procollagen genes, COL1A1 or COL1A2. The disorder is characterized by bone fragility leading to increased fracture incidence and long-bone deformities. Although multiple mechanisms underlie OI, endoplasmic reticulum (ER) stress as a cellular response to defective collagen trafficking is emerging as a contributor to OI pathogenesis. Herein, we used 4-phenylbutiric acid (4-PBA), an established chemical chaperone, to determine if treatment of Aga2+/- mice, a model for moderately severe OI due to a Col1a1 structural mutation, could attenuate the phenotype. In vitro, Aga2+/- osteoblasts show increased protein kinase RNA-like endoplasmic reticulum kinase (PERK) activation protein levels, which improved upon treatment with 4-PBA. The in vivo data demonstrate that a postweaning 5-week 4-PBA treatment increased total body length and weight, decreased fracture incidence, increased femoral bone volume fraction (BV/TV), and increased cortical thickness. These findings were associated with in vivo evidence of decreased bone-derived protein levels of the ER stress markers binding immunoglobulin protein (BiP), CCAAT/-enhancer-binding protein homologous protein (CHOP), and activating transcription factor 4 (ATF4) as well as increased levels of the autophagosome marker light chain 3A/B (LC3A/B). Genetic ablation of CHOP in Aga2+/- mice resulted in increased severity of the Aga2+/- phenotype, suggesting that the reduction in CHOP observed in vitro after treatment is a consequence rather than a cause of reduced ER stress. These findings suggest the potential use of chemical chaperones as an adjunct treatment for forms of OI associated with ER stress. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
Keywords: Collagen Type I; modely nemocí na zvířatech; molekulární chaperony; fenotyp; Phenotype; mutace; osteogeneze; Bip+/−; osteoblasty; kolagen typu I; Osteoblasts; Molecular Chaperones; ER stress; Chop−/−; Butylamines; Animals; osteogenesis imperfecta; 4-PBA; zvířata; Disease Models, Animal; myši; butylaminy; Mutation; Osteogenesis; Mice; Osteogenesis Imperfecta; Aga2; bone